Boating-related drowning in Australia: Epidemiology, risk factors and the regulatory environment. (September 2019) - Willcox-Pidgeon, Stacey; Peden, Amy E.; Franklin, Richard C.; Scarr, Justin
Abstract: Objective : Recreational boating is a popular pastime in many high income countries, and is a leading activity prior to drowning. This study reports on unintentional fatal drowning associated with boating-related incidents in Australia. Methods : A total population, retrospective, cross sectional design examined all boating-related unintentional drowning deaths between July 1, 2005 and June 30, 2015. Variables examined included age, sex, location of drowning incident, vessel type, activity, presence of alcohol/drugs, and lifejacket wear. Relative risk (with a 95% confidence interval) was calculated using fatal drowning rates per 100, 000 population and rates per 100, 000 registered vessels. Chi square analysis and non-parametric tests for significance were applied. Statistical significance was deemed p < .05. Results : A total of 415 people drowned while boating during the study period, 91.8% male and 35.7% aged between 25 and 44 years. Men were 10 times more likely to drown when boating than females (RR = 10.64 CI:7.55–14.97). Over one-quarter (28.7%) of incidents involved alcohol, in 30.6% drugs were identified (31.3% were illegal) and 90.4% were not wearing a lifejacket. Children were more at risk of drowning on a houseboat than adults (RR = 7.13; CI:1.61–31.61). Females were more likely to drown than males when using a personal watercraft (RR = 10.53; CI:2.75–40.33). Conclusion : Boaters may be taking unnecessary risks by disregarding safety regulations, such as not wearing lifejackets and substance use (such as alcohol and illegal drugs). Boating in remote locations presents a high risk of drowning. While safety regulations are in place, enforcement and behavior change remain challenges. Practical application: Findings support recommendations for increased enforcement of alcohol-related regulations and introducing drug-testing for boaters. Consistency of boating safety regulations, especially around lifejacket wear, is recommended to influence behavior change. The effectiveness of current lifejacket regulations need to be critically evaluated in the context of increasing wear rates for adults and children. Highlights: Legislation in isolation has had varied success in reducing boating-related drowning deaths. This study is the first national study to examine boating related fatal drowning per 100, 00 recreational powered boats. Boating in remote locations presents the highest risk of drowning; a relative risk 27 times (RR 27.13; CI:10.91–67.45) that of major cities. Only 10% who drowned when boating in Australia were known to be wearing a lifejacket. Increased enforcement of substance-use related boating legislation is recommended.